2015
DOI: 10.1080/13803395.2015.1037252
|View full text |Cite
|
Sign up to set email alerts
|

Information processing speed and attention in multiple sclerosis: Reconsidering the Attention Network Test (ANT)

Abstract: Deficits in processing speed are more prominent in MS than those involving attention, and when the former are properly accounted for, differences in the latter are confined to the alerting network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
(68 reference statements)
0
12
0
2
Order By: Relevance
“…Several studies investigated the impact of PS decline on cognition in people with MS. It was observed that in tasks of working memory [14,23], response inhibition [21], planning [20], task switching [24], and attention [25], after statistically controlling for PS performance, the differences between people with MS and healthy controls disappeared.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated the impact of PS decline on cognition in people with MS. It was observed that in tasks of working memory [14,23], response inhibition [21], planning [20], task switching [24], and attention [25], after statistically controlling for PS performance, the differences between people with MS and healthy controls disappeared.…”
Section: Introductionmentioning
confidence: 99%
“…Slowed PS has broader repercussions on performance in other cognitive domains [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Early stages of MS have been associated with significant cognitive impairment focused on attention, executive functions, memory, and learning [16]. Information processing in particular is the cognitive domain most widely affected by MS and is notably the first deficit to emerge [1719]. MS patients with progressive disease course, especially secondary progressive, can also experience a range of cognitive deficits and associated disability [20].…”
Section: Introductionmentioning
confidence: 99%